Capital market exposure of BRAC Bank Limited - Saha, Rumpa (BRAC University, 2012)
An Internship Report Presented to the Faculty of Business Administration in Partial Fulfillment of the Requirements for the Degree of Bachelor of Business Administration, BRAC University.